Legal Discourse on Contract Marriage in Indonesian and Islamic Law - Izzat, Akrimatil; Mulki, Siti Afifah Ahmed (Faculty of Law, Universitas Negeri Semarang, 2022)
Contract marriage, also known as temporary or mut’ah marriage, has garnered significant attention within both Indonesian civil law and Islamic legal frameworks. This paper examines the legal discourse surrounding contract marriage in Indonesia, juxtaposing it with principles derived from Islamic jurisprudence. Through a comprehensive analysis of legal texts, court cases, and scholarly opinions, this study explores the complexities and divergent interpretations surrounding the validity, implications, and societal perceptions of contract marriage in Indonesia. The paper begins by delineating the historical background and evolution of contract marriage within Indonesian society, tracing its roots in Islamic tradition and its assimilation into the legal framework of the nation. Subsequently, it delves into the multifaceted legal perspectives on contract marriage, scrutinizing debates regarding its legality, morality, and socio-cultural implications. Furthermore, this paper scrutinizes the judicial stance on contract marriage, examining landmark court cases and legal precedents that have shaped its legal status and societal reception. It also evaluates the role of religious authorities and their interpretations of Islamic law concerning contract marriage, shedding light on the discrepancies between legal theory and practical implementation. Moreover, the paper explores the socio-cultural ramifications of contract marriage within Indonesian society, analyzing its impact on gender dynamics, familial structures, and broader social norms. The study investigates the intersections of contract marriage with issues such as women's rights, marital stability, and religious identity, providing insights into the complex interplay between legal, religious, and socio-cultural factors.